TRAINING: DIGITALIZATION-BASED HUMAN RESOURCE EMPOWERMENT ON SOCIAL MEDIA AND MARKETING 5.0 NAMIRA ISLAMIC SCHOOL MEDAN - Nur Aisyah; Riza Fanny Meutia; Sairah Sairah (Yayasan Education and Social Center, 2023)
This research provides an overview of strengthening human resource management. It aims to provide training and socialization in motivating teachers at Namira Islamic School to explore their respective potentials to make themselves solid individuals and have the desire as individuals who can use IT in the form of digitizing the learning process for themselves and the environment, as an improvement in the performance of human resource management at Namira Islamic School. Then it will influence the environment or students of Namira Islamic School with a positive thinking pattern and can invite and provide an activity and make it a role that follows the technological developments of an educator in particular and generally to the environment of the Republic of Indonesia. Strengthening that motivates to explore self-potential in confidence in the ability of self-potential in increasing knowledge of digitization of human resource management in the use of social media by the development of increasingly advanced IT